Psychosocial Adaptation in Relatives of Critically Injured Patients Admitted to an Intensive Care Unit - Martín Rodríguez, Agustín; Pérez San Gregorio, Mª Ángeles (The Spanish Journal of Psychology, 2005)
The aim of this study is to analyze how the length of time a patient spends in an Intensive Care Unit (ICU) affects close relatives, with regard to specific clinical variables of personality, family relationships and fear of death. The study group consisted of 57 relatives of seriously ill patients admitted to the ICU of “Virgen del Rocío” Rehabilitation and Trauma Hospital (Seville, Spain). The instruments applied were: a psychosocial questionnaire, clinical analysis questionnaire, family environment scale and fear of death scale. The relatives of patients admitted to ICU obtained higher scores in hypochondria, suicidal depression, agitation, anxious depression, guilt-resentment, paranoia, psychasthenia, psychological maladjustment and self-expression, and less in fear of their own death, as when compared to interviews with the same relatives 4 years later. The length of time a patient spent in the ICU influenced relatives in some clinical variables of personality, family relationships and fear of death.